Confidences: Talks With a Young Girl Concerning Herself - Lowry, E. B. (Edith Belle), 1878-1945 (Salt Lake City, UT : Project Gutenberg, 2004)
"Confidences: Talks With a Young Girl Concerning Herself" by E. B. Lowry is a guidebook intended for young girls, likely written in the early 20th century. This book serves to educate girls aged ten to fourteen about their bodies, health, and the natural processes of growing up, with a focus on creating an open conversation between mothers and daughters. It aims to empower young girls with knowledge that fosters self-care and understanding of their development. The content of the book is structured as a series of engaging discussions between a narrator and a young girl named Violet. It covers various topics from the biological aspects of plants and animals to the intricacies of the female body, including menstruation and the importance of a healthy lifestyle. The narrative illustrates the parallels between flowers, birds, and girls, emphasizing the value of nurturing one's body and understanding the life processes involved in becoming a mother. Each chapter combines scientific facts with compassionate insights, encouraging young girls to embrace their natural development while equipping them with the knowledge to maintain their health and well-being. (This is an automatically generated summary.)
Release date is 2004-12-24
Produced by David Garcia and the Online Distributed Proofreading Team.
Keywords: Sex instruction